Sodium leak through K2P potassium channels and cardiac arrhythmia, an emerging theme - Steve AN Goldstein (EMBO Molecular Medicine)
Abstract In this issue of EMBO Molecular Medicine, Decher et al (2017) identify a point mutation in the K2P2 (TREK‐1) potassium (K+) channel that changes function in just those ways expected to predispose to right ventricular outflow tract (RVOT) ventricular tachycardia (VT) in the patient they study. Whereas wild‐type channels are selective for K+ and inhibited by β‐adrenergic stimulation, mutant I267T channels pass sodium (Na+) into the cells, even during β‐adrenergic stimulation, and are more active in response to membrane stretch, changes predicted to enhance cardiac myocyte excitability. The report contributes to accumulating evidence for Na+ leak via K2P channels in association with normal development (Thomas et al, 2008), acquired arrhythmia (Ma et al, 2011), and now a missense mutation. Decher et al (2017) both inform and direct us toward interesting opportunities for further investigation.